2009
DOI: 10.1152/ajpgi.90620.2008
|View full text |Cite
|
Sign up to set email alerts
|

p53 inhibition of AP1-dependent TFF2 expression induces apoptosis and inhibits cell migration in gastric cancer cells

Abstract: Overexpression of trefoil factor 2 (TFF2) is associated with increased cell migration, resistance to apoptosis, and possibly increased gastric cancer invasion. Dysregulation of p53 is frequently observed in preneoplastic conditions of the stomach. Here, we investigated the effect of p53 on the expression and function of TFF2 in gastric cancer cell lines. Gene expression was determined by reverse transcription-polymerase chain reaction, and promoter activity was assessed by dual luciferase reporter assays. Apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Other positional relationships included factors involved in environmental stress and oncogenesis such as AP1, NRF2, FOXO3 and ETS/SPI1/PU.1, and pluripotent stem cell maintenance such as Oct4, Sox2, Klf4, and Myc, or related family members. A number of these factors have been demonstrated to have functional interrelationships with p53 (Renault et al, 2011; Rotblat et al, 2012; Tu et al, 2009; Zhu et al, 2006). Approximately 1,000 paired genomic features were identified ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other positional relationships included factors involved in environmental stress and oncogenesis such as AP1, NRF2, FOXO3 and ETS/SPI1/PU.1, and pluripotent stem cell maintenance such as Oct4, Sox2, Klf4, and Myc, or related family members. A number of these factors have been demonstrated to have functional interrelationships with p53 (Renault et al, 2011; Rotblat et al, 2012; Tu et al, 2009; Zhu et al, 2006). Approximately 1,000 paired genomic features were identified ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A 950 bp fragment of the Beclin 1 promoter was cloned into the pGL3-Basic vector through PCR amplification from human genomic DNA (Promega) using synthetic primers (23). MKN-28 cells (1.0×10 5 cells/12-well) were transfected with 1.5 μg Beclin 1-luciferase or 1.5μg empty reporter vector DNA using the FuGene HD transfection reagent (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…After 6 hours, the transfected cells were cultured either with or without 20ng/ml IFN-γ for 24-hours. Luciferase activity was determined as previously described (23). All assays were performed in triplicate and repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…XIAP has been shown to be overexpressed in most human cancer cell lines and cancer tissues including HCC tissues. Its overexpression has been demonstrated to be the independent factor for predicting the poor prognosis of HCC patients after liver transplantation [8]. Studies have shown that XIAP antisense nucleic acid and small molecule inhibitors of XIAP induce apoptosis and inhibit tumor growth in HCC cells [9], indicating that targeting inhibition of XIAP may be a new approach for HCC therapy [10].…”
Section: Introductionmentioning
confidence: 99%